Place-based assessment of sociability of shopping streets in the Kuala Lumpur City Centre, Malaysia - Rakhshanifar, Mahboubeh (2019)
The functions of streets as social places have been undermined by the emergence of modern shopping malls that focus on indoor social activities. Streets mainly use as channels for vehicular movement rather than spaces for social activities due to the dominance of car-oriented environment. In the context of Kuala Lumpur city, in spite of the high intensity of pedestrians in the main shopping streets, low social activities observed. The lack of social activities in the main shopping streets could be due to the quality of the physical and the social environmental characteristics. The aim of the research is to determine the street sociability based on the assessment of the people-based and place-based characteristics of selected shopping streets in Kuala Lumpur.